Clinical significance of residual fragments in 2015: impact, detection, and how to avoid them - Hein, Simon; Rassweiler, Jens (World journal of urology, 2016)
Purpose Residual fragments are common after stone treatment. Little is known about clinical outcomes relevant to the patient. This comprehensive review of the literature highlights the impact of residual fragments, modes of detection, and treatment strategies to avoid residual fragments in shock wave therapy, ureteroscopy, and percutaneous nephrolithotomy. Methods A comprehensive review of current literature was performed using PubMed®, MEDLINE®, Embase™, Ovid®, Google Scholar™, and the Cochrane Library. Publications relevant to the subject were retrieved and critically appraised. Results Residual fragments after treatment for urinary stones have a significant impact on a patient’s well-being and future course. (Ultra-) low-dose non-contrast computed tomography detects small residuals most reliably. In shock wave lithotripsy, adherence to basic principles helps to improve results. Various techniques and devices facilitate complete stone clearance in conventional and miniaturized percutaneous nephrolithotomy and (flexible) ureteroscopy. Promising new technologies in shock waves, lasers, and robotics (and potentially microrobotics) are on the horizon. Conclusions Residual fragments are relevant to patients. Contemporary treatment of urolithiasis should aim at complete stone clearance.